The New Neighborhood Watch: An Exploratory Study of the Nextdoor App and Crime Narratives - Parker, Megan; Dodge, Mary (International Journal of Criminology and Sociology, 2024)
Community members use the Nextdoor App to prevent crime and circulate information when suspicious activity or criminal misconduct is afoot. The Nextdoor App operates like other popular social media platforms, but unlike Facebook and Twitter, it connects citizens based on geography instead of areas of interest. One unique aspect of the app is posting events and perceptions of suspicious behavior and criminal acts. User posts can provide narratives on feelings, incidents, and perceptions of crime in designated neighborhoods. This exploratory study focuses on how community members in an urban Colorado area use the app as a high-tech Neighborhood Watch. A qualitative research approach with a thematic analysis is implemented to examine neighbors’ perceptions of crime events and community safety. The findings depict that citizens engaged in Nextdoor communications are frustrated with petty community incivilities, property crimes, and law enforcement actions. In addition, the results show that lessons in being a capable guardian, possible increases in fear levels, and surveillance activities are important aspects of understanding social media and crime.